2013
DOI: 10.1002/pssc.201200617
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature operation of ITO nano‐crystal gas sensor

Abstract: We proposed an indium‐tin‐oxide (ITO) based gas sensor which can operate at room temperature. ITO nano‐crystal was screen printed on a quartz substrate. To improve the sensitivity and to decrease the resistivity of the printed ITO layer, pressurized annealing was adopted. Resistivity of the printed ITO gas sensor decreased from 3.5 kΩcm to 1.56 Ωcm by pressurized annealing. We could observe room temperature operation of the printed ITO gas sensor by using various gases such as Ar, N2, O2 and CH4. (© 2013 WILEY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It has already been demonstrated that the screen printing of organometallic precursor paste followed by firing at high temperatures (600 °C) for a relatively long time (for 40 min at optimum for ITO crystallization) can be utilized for sensor fabrication [ 6 ]. The latest efforts demonstrated the suitability of screen printing for pastes directly composed from ITO nanocrystals and binders for sensor fabrication [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been demonstrated that the screen printing of organometallic precursor paste followed by firing at high temperatures (600 °C) for a relatively long time (for 40 min at optimum for ITO crystallization) can be utilized for sensor fabrication [ 6 ]. The latest efforts demonstrated the suitability of screen printing for pastes directly composed from ITO nanocrystals and binders for sensor fabrication [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%